Respostas

2014-07-23T18:11:06-03:00
Olá, Ivy159357!

x² - 5x + 6 = 0
a = 1
b = -5
c = 6

Δ = b² - 4.a.c
Δ = (-5)² - 4.1.6
Δ = 25 - 24
Δ = 1

-b +- √Δ / 2.a
-(-5) +- √1 / 2.1
5 +- 1 /2

x' = 5+1/2 = 6/2 = 3
x'' = 5-1/2 = 4/2 = 2



1 5 1
2014-07-23T18:19:21-03:00
X² - 5x + 6 = 0 onde x² é a, -5x é b e 6 é c

Δ = b² - 4 x a x c
Δ = (-5)² - 4 x 1 x 6 
Δ = 25 - 24
Δ = 1

X = -b +/- √Δ => dividido por 2 x a
X = - (-5) +/- 1 => dividido por 2 x a

Agora vamos achar X¹
X¹ = 5 + 1 dividido por 2 x 1 
X¹ = 6/2 = 3

Agora vamos achar X²
X² = 5 - 1 dividido por 2 x 1
X² = 4/2 = 2

Logo as raízes são 3 e 2. Espero ter ajudado.